A remarkable permeability enhancement of Ni1−xZnxFe2O4 (x = 0.65 and 0.70), using a multi-compound calcined additive - S. Shatooti; M. Mozaffari (Scientific Reports)
Abstract In this study, entanglement of composition, additive and/or sintering conditions and their effects on magnetic properties of soft ferrites, nickel zinc spinel ferrites (Ni1−xZnxFe2O4, x = 0.65 and 0.70) which were prepared via conventional solid-state reaction method investigated. Also an equiponderant calcined mixture of Bi2O3, CaO, CeO2, SiO2, Al2O3, Y2O3 and nanotitania was mixed thoroughly and used as a multi-compound calcined additive (MCCA). Calcined ferrite powders were crushed, dry and wet milled, dried, mixed with different amounts of MCCA (0.0, 0.5, 1.0, 1.5 and 2.0 wt%), formed in toroidal shapes and finally sintered at different temperatures, from 1150 up to 1360 °C for 3 h. X-ray diffraction assessment confirmed formation of the single phase cubic spinel structures. Initial permeability and Q-factor spectra of the toroids were obtained from 0.1 to 1000 kHz, using an LCR meter. The results show that initial permeability of each sample has a maximum and addition of MCCA to the ferrites leads to a marvelous increase in permeabilities. Additionally, MCCA decreases the optimum sintering temperature too. The optimum amounts of additive were 1.0 and 0.5 wt% for the x = 0.65 (μ′ = 492, Ts = 1280 °C) and x = 0.70 (μ′ = 478, Ts = 1320 °C), respectively. Permeability spectra illustrate that utility zone of the Ni0.35Zn0.65Fe2O4 and Ni0.3Zn0.7Fe2O4 are both less than 100 and 10 kHz, respectively. The results represent that there is a strong entanglement between composition, additive and/or sintering conditions. It can be concluded the MCCA added Ni0.35Zn0.65Fe2O4, is suitable for application in the switching power supplies.